Detection of N, N-diacetyllactosamine (LacdiNAc) containing free prostate-specific antigen for early stage prostate cancer diagnostics and for identification of castration-resistant prostate cancer patients. (1st June 2021) - Bertokova, Aniko; Bertok, Tomas; Jane, Eduard; Hires, Michal; Ďubjaková, Petra; Novotná, Oľga; Belan, Vitazoslav; Fillo, Juraj; Tkac, Jan
Graphical abstract: Principal component analysis applied for clustering of patients with benign prostatic hyperplasia (left) and patients with prostate cancer (right). Outside the cluster are patients with changed glycosylation of free form of prostate specific antigen compared to the rest of the patients in the cohort. PCA applied for identification of castration resistant prostate cancer patients in the BPH cohort. Highlights: Analysis of changes in the glycan composition of free form of prostate specific antigen (fPSA) was done in ELISA format. Individual and Double biomarkers were applied to discriminate benign prostate hyperplasia patients (BPH) from prostate cancer (PCa) patients. The best double biomarker is gPSA (glycan form of fPSA) and PSAd (PSA/prostate volume) Such biomarker offers high discrimination power BPH vs. PCa with AUC (area under receiver operating curve) of 0.896. Genetic algorithm was applied to identify false negatives in the benign cohort. Principal component analysis (PCA) applied for identification of prostatis patient in the BPH cohort; Abstract: Prostate cancer (PCa) is one of the most common cancer types among men and also a common cause of death globally. With an increasing incidence, there is a need for low-cost, reliable biomarkers present in samples, which could be provided non-invasively (without a need to perform prostate biopsy). Glycosylation changes of free-PSA (fPSA) are considered cancer-specific, while the level of different PSA forms can increase under other than cancerous conditions. In the present study, we investigated the role of  N, N -diacetyllactosamine (LacdiNAc) epitope of fPSA ( i.e. glycoprofile of fPSA or gPSA) in combination with total-PSA (tPSA), prostate volume, and tPSA density (tPSA level divided by prostate volume i.e. PSAd) as biomarkers for monitoring of PCa development and progression in 105 men. Furthermore, we applied an genetic (evolutionary) algorithm to identify any suspicious individuals in a benign cohort having benign prostatic hyperplasia (BPH). We identified 3 suspicious men originally diagnosed with BPH using gPSA analysis. In the follow-up we found out that two men should not be considered as BPH patients since multiparametric magnetic resonance imaging (mpMRI) identified one man with clinically significant PCa via Prostate Imaging – Reporting and Data System (PI RADS v2 = 4) and the second man was with High-grade prostatic intraepithelial neoplasia (HG PIN), commonly described as a pre-cancerous stage. Moreover, in the study we described for the first time that changed LacdiNAc on PSA can be applied to identify prostatitis patients and most importantly this is the first study suggesting that changed glycosylation on PSA can be applied to identify castration-resistant prostate cancer (CRPCa) patients.